SPECT in the Kleine–Levin Syndrome, a Possible Diagnostic and Prognostic Aid? - Vigren, Patrick; Engström, Maria; Landtblom, Anne-Marie (Frontiers in Neurology, 2014)
INTRODUCTION: Kleine-Levin syndrome (KLS) is a rare syndrome of periodic hypersomnia and behavioral and cognitive symptoms based on clinical criteria. In the setting of differential diagnosis of hypersomnia disorders, an objective diagnostic aid is desirable. A promising modality is single photon emission computed tomography (SPECT). As intraepisodal investigations are difficult to perform, an interepisodal investigation would be very helpful. Another aim of the study was to correlate SPECT findings to prognosis. METHODS AND MATERIAL: 24 KLS-patients were categorized as severe or non-severe based on clinical characteristics. The clinical characteristics were analyzed in relation to SPECT-examinations performed between hypersomnia periods (interepisodal) or after remission, as a clinical routine investigation. RESULTS: 48% of the KLS-patients have hypoperfusion in the temporal or fronto-temporal regions. In patients that have undergone remission, 56% show that pattern. There were no specific findings related to prognosis. DISCUSSION/CONCLUSION: SPECT might be a diagnostic aid, in a setting of hypersomnia experience. With a sensitivity of 48%, interepisodal SPECT alone cannot be used for diagnosing KLS.